Antimicrobial Food Packaging System Based on Ethyl Lauroyl Arginate-Loaded Core/Shell Electrospun Structures by Using Hydrophilic and Hydrophobic Polymers - Galotto-Lopez, M; Lopez de Dicastillo-Bergamo, A; Patiño-Vidal, C; Velasquez, E (Elsevier Ltd, 2021)
Antimicrobial compounds can be encapsulated into core/shell structures through coaxial electrospinning in order to develop novel active food packaging materials. In this work, poly (vinyl alcohol)-(ethyl lauroyl arginate)/poly (lactic acid) core/shell fibers, (PVOH-LAE/PLA)f, were developed with the purpose to study the influence of combining a hydrophilic and a hydrophobic polymer on LAE release. LAE release studies were carried out in an aqueous and fatty food simulant, and data were analyzed through a phenomenological mass transfer model. Flat-ribbon fibers with a core/shell structure were observed by TEM. PLA crystallinity degree of coaxial fibers did not present significant differences with uniaxial PLA fibers, although thermal stability and the glass transition temperature decreased. The maximum concentrations of LAE released from (PVOH-LAE/PLA)f fibers to both simulants reached the MIC values of LAE against Listeria innocua, evidencing a higher affinity of LAE towards fatty simulant and a fast diffusion from fibers in the aqueous simulant. © 2020
Keywords: Electrospinning; Ethyl lauroyl arginate; Core/shell fiber; Antimicrobial; Food packaging